ADB's third decade 1987-1996 updated edition. (ADB through the decades., 2017)
This third volume from the series ADB through the Decades presents ADBs response to expert recommendations for a new role for ADB in the 1990s, and greater emphasis on effectiveness in the delivery of development assistance.